2000
DOI: 10.1016/s0022-5223(00)70218-2
|View full text |Cite
|
Sign up to set email alerts
|

Autologous porcine heart cell transplantation improved heart function after a myocardial infarction

Abstract: Autologous porcine heart cell transplantation improved regional perfusion and global ventricular function after a myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(81 citation statements)
references
References 14 publications
2
77
0
2
Order By: Relevance
“…This cell loss may be partially offset by natural regeneration of cardiac myocytes in adult hearts (6). Cell transplantation to treat heart disease has been studied in various animal models (9,14,16,19,25). Cell types used include ventricular cardiomyocytes, skeletal myoblasts, smooth muscle cells, fetal and embryonic cardiomyocytes, bone marrow stromal, hematopoietic stem cells, and mouse embryonic stem (ES) cells (9,14,16,19,25).…”
mentioning
confidence: 99%
“…This cell loss may be partially offset by natural regeneration of cardiac myocytes in adult hearts (6). Cell transplantation to treat heart disease has been studied in various animal models (9,14,16,19,25). Cell types used include ventricular cardiomyocytes, skeletal myoblasts, smooth muscle cells, fetal and embryonic cardiomyocytes, bone marrow stromal, hematopoietic stem cells, and mouse embryonic stem (ES) cells (9,14,16,19,25).…”
mentioning
confidence: 99%
“…Studies in animal models have shown that transplantation of fetal stem cell, ES cells, or pluripotent stem cell derivatives can successfully treat many chronic diseases, such as Parkinson's disease, diabetes, traumatic spinal cord injury, Purkinje cell degeneration, Duchenne's muscular dystrophy, liver or heart failure, and osteogenesis imperfecta (Zhang et al, 1996;Horwitz et al, 1999;McDonald et al, 1999;Kobayashi et al, 2000;Li et al, 2000;Soria et al, 2000;Kim et al, 2002). Almost every day there are reports in the media of new stem cell therapies.…”
Section: Resultsmentioning
confidence: 99%
“…Fetal and neonatal cardiomyocytes have been tested for this purpose [62,63]. However, the implanted cardiomyocytes were unable to integrate with the native myocardium and caused arrhythmias [64]. In addition, the source for human fetal or neonatal cardiomyocytes is a concern.…”
Section: Cells Available For Deliverymentioning
confidence: 99%